Effects of salinity stress on some characteristics of germination and seedling growth of mike thistle (Silybum marianum) and Thistle (Echinops candidus - قاسم پرمون; علی عبادی; معصومه اسدی آقبلاغی (علوم و فناوری بذر ایران, 2015)
In order to study of salinity effects on seed germination and seedling growth of milk thistle and thistle, an experiment was carried out. Experiment was factorial based on a completely randomized design with three replications. Treatments included seeds of wild species milk thistle and thistle and five salinity levels (0, 50, 100, 150 and 200 mM NaCl). Results showed that salinity leads to decrease in germination percentage, germination rate and increase in mean germination time that these changes were more in thistle compared to milk thistle. Seedling growth indices (length and fresh and dry weight of cotyledon and hypocotyl) were also affected by salinity. Most traits of thistle were not affected by salinity (50 mM) in comparison with milk thistle, whereas these changes were higher in levels of salinity and this result indicated more relative tolerance to salinity in thistle. However, salinity caused to decline primary and secondary vigor and seed reserve use efficiency, but seed reserve using rate decreased under stress condition. The amount of Na+, K+ and Ca2+ in radicle increased in low levels of salinity and decreased by enhancing of stress intensity.